Comparative study of the solvolytic deconstruction of corn stover lignin in batch and flow-through reactors. Issue 19 (15th September 2021) - Vincent Sahayaraj, Daniel; A, Lusi; Mitchell, Emma M.; Bai, Xianglan; Tessonnier, Jean-Philippe
Abstract : Deconstruction of corn stover lignin in a flow-through reactor enhanced product yields 2-fold compared to batch systems. It also showed beneficial effects on aromatic hydrocarbons formed during catalytic fast pyrolysis compared to the parent lignin. Abstract : Solvolysis of industrial corn stover lignin was carried out in methanol and ethanol to deconstruct lignin into monomers and small oligomers using various reactor configurations. We demonstrate that it is possible to overcome the limitations inherent to batch reactors by carrying out the solvolytic deconstruction in flow-through reactor systems as they allow for the continuous removal and rapid cooling of the products. Monomers and solvent-soluble product yields achieved in flow-through reactors were higher under all tested reaction conditions. We also investigated the effects of various reaction parameters and phase of solvent (sub- and supercritical) on the distribution and yield of lignin-derived products using complementary characterization techniques. p -Coumaric acid and ferulic acid were obtained as primary monomers with very high selectivity and a maximum monomer yield of 14.45 wt% was achieved at 250 °C and 85 bar in ethanol. Subsequent upgrading of the deconstructed fractions through fast pyrolysis was also studied. In addition to the increased yield of phenolic monomers (23.86 wt% vs. 10.29 wt%), char formation during pyrolysis was substantially decreased (26.36 wt% vs. 40.95 wt%) under optimized conditions. The beneficial impact of the solvolytic pretreatment was also reflected in an enhanced aromatic hydrocarbon yield during catalytic fast pyrolysis.